Estudo dose-resposta e perfil de expressão gênica do herbicida diuron [3-(3,4-diclofenil)-1,1-dimetiluréia] em bexiga urinária de ratos wistar machos - Ihlaseh, Shadia Muhammad [UNESP] (2011)
Diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is a substituted urea herbicide that at high dietary levels (2500 ppm) induces rat urinary bladder urothelial hyperplasia in 20 weeks and neoplasia in 2 years. The effects on the urothelium in a short period of exposure, however, have not been described. The present 7-day study evaluated the dose-dependent effects of urothelial alterations in the urinary bladder using histology, scanning-electron microscopy (SEM) and transcriptional profiling with Affymetrix microarrays. Six-week old male Wistar rats were treated with 0, 125, 500, 2500 ppm of diuron in the diet for 7 days. The numbers of differentially expressed genes (DEGs) in the exposed groups increased with dose. Diuron affected several functions involved with cell-to-cell interaction and tissue disorganization at transcriptional level, however, 7 days of exposure seemed to be insufficient to cause morphological lesions. Comparison of the gene expression observed at 7-day and 20- week time points indicates more differences than similarities. The present data suggests an initial adaptive response to protect the urothelium to the continuous exposure to diuron. By the 20th week, the protective response is suppressed and the mucosa develops simple hyperplasia, a morphologic consequence of cytotoxicity and necrosis followed by a continuous replacement of the epithelium. This process can explain the development of urothelial bladder tumors at the end of a 2-year exposure to diuron.